Construction of a Promising Tumor-Infiltrating CD8+ T Cells Gene Signature to Improve Prediction of the Prognosis and Immune Response of Uveal Melanoma - Sun, Yifang; Wu, Jian; Yuan, Yonggang; Lu, Yumin; Luo, Ming; Lin, Ling; Ma, Shengsheng (Frontiers in Cell and Developmental Biology, 2021)
Background: CD8+ T cells work as a key effector of adaptive immunity and closely associate with immune response for killing tumor cells. It is crucial to understand the role of tumor-infiltrating CD8+ T cells in uveal melanoma (UM) for the prognosis and response to immunotherapy. Methods: Using single-cell sequencing transcriptomes of UM and immune related genes to screen the CD8+ T cells associated immune related genes (CDIRGs) for subsequent analysis. Next, a prognostic gene signature referred to tumor-infiltrating CD8+ T cells was constructed and validated in several UM bulk RNA-seq datasets. The risk score of UM patients was calculated and classified into high or low subgroup and its prognostic value was estimated by using multivariate Cox analysis and Kaplan-Meier survival analysis. Moreover, the potential ability of gene signature for immunotherapy response was further explored. Results: In total, 202 CDIRGs screened out from the single-cell RNA-seq of GSE139829. Next, a gene signature contained 3 CDIRGs (IFNGR1, ANXA6 and TANK) was identified, which considered as an independent prognostic indicator to robustly predict overall survival (OS) and metastasis-free survival (MFS) of UM. In addition, the UM patients were classified into high and low risk subgroups with different clinical characteristic, CD8+ T cell immune infiltration and immunotherapy response. Gene Set Enrichment Analysis (GSEA) showed that immune pathways such as allograft rejection, inflammatory response, interferon alpha and gamma response, antigen processing and presentation were all positively activated in low risk phenotype. Conclusions: Our work gives an inspiration to explain the limited response for the current immune checkpoint inhibitors to UM. Besides, we constructed a novel prognostic and immunotherapy responses related gene signature for tumor-infiltrating CD8+ T cell targeting treatment approaches.